The effectiveness of influenza vaccination among nursery school children in China during the 2016/17 influenza season. Issue 18 (25th April 2018) - Wang, Yin; Chen, Liling; Yu, Jia; Pang, Yuanyuan; Zhang, Jun; Zhang, Tao; Zhao, Genming
Highlights: The overall influenza vaccine effectiveness during 2016/17 was 20.6%. The incidence of developing ILI symptoms was lower among vaccinated. The incidence of seeking health-care behaviors were lower among vaccinated. Abstract: Background: The effectiveness of influenza vaccine among nursery school children has not been systematically studied. We conducted a cohort study of children from 13 nursery schools in Suzhou, China, to estimate the effectiveness of influenza vaccine against laboratory-confirmed influenza during 2016–17. Methods: Children aged 36–72 months were chosen from 13 nursery schools from 3 District in Suzhou. The surveillance started 2 weeks after vaccination during October 2016–February 2017. Class teachers reported the names of students with ILI (influenza-like illness) to study clinicians on each school day. Further, local physicians collected the student's nasopharyngeal swab or throat swab, either at a study clinic or at the child's home. The swabs were sent to the National Influenza Network Laboratory in Suzhou Center for Disease Control and Prevention for influenza testing by RT-PCR. Result: A total of 4614 children were enrolled, of which 15 children (vaccinated: 2; unvaccinated: 13) were lost to follow-up. Of the remaining 4599 children, 558 swabs were collected. Among these swabs, 70 samples tested positive for influenza virus; 17 in the vaccinated group (B Victoria: 2; H3N2: 15) and 53 in the unvaccinated group (B Victoria: 14; A(H1N1)pdm09: 1; H3N2: 38). The overall influenza vaccine effectiveness (VE) during the influenza season of 2016–2017 was 20.6%. The incidence of developing ILI symptoms and healthcare seeking behavior through clinical visits was significantly lower in vaccinated children than in the unvaccinated group. Conclusion: Influenza vaccine protection in vaccinated and unvaccinated children showed no statistical difference and the VE percentage varied for different virus subtypes. However, the incidence rate of developing ILI and healthcare seeking behavior was significant lower in the vaccinated group than in the unvaccinated children. Larger studies are required to estimate the VE according to the influenza type, subtype, and lineage during influenza seasons in China in the future.